2016
DOI: 10.1002/cbic.201500504
|View full text |Cite
|
Sign up to set email alerts
|

Probing Protein Surfaces: QSAR Analysis with Helix Mimetics

Abstract: α-Helix-mediated protein-protein interactions (PPIs) are important targets for small-molecule inhibition; however, generic approaches to inhibitor design are in their infancy and would benefit from QSAR analyses to rationalise the noncovalent basis of molecular recognition by designed ligands. Using a helix mimetic based on an oligoamide scaffold, we have exploited the power of a modular synthesis to access compounds that can readily be used to understand the noncovalent determinants of hDM2 recognition by thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
0
4
0
1
Order By: Relevance
“…The assay relies upon binding of ethidium bromide to unhydrolysed RNA 48. Using the remaining fluorescence as an approximation of activity, we used the assay to screen libraries of previously prepared aromatic oligoamide helix-mimetics (see ESI for structures; ESI Tables S1 and S2†) derived from O -alkylated,44,49,50 N -alkylated14 and hybrid scaffolds,43,51 for reactivation of the S-protein (ESI Fig. S1†).…”
Section: Resultsmentioning
confidence: 99%
“…The assay relies upon binding of ethidium bromide to unhydrolysed RNA 48. Using the remaining fluorescence as an approximation of activity, we used the assay to screen libraries of previously prepared aromatic oligoamide helix-mimetics (see ESI for structures; ESI Tables S1 and S2†) derived from O -alkylated,44,49,50 N -alkylated14 and hybrid scaffolds,43,51 for reactivation of the S-protein (ESI Fig. S1†).…”
Section: Resultsmentioning
confidence: 99%
“…In order to understand the rules that govern the molecular recognition between peptidomimetics and proteins, new oligoamide-based scaffold with an intercalated α-amino acid were studied on the p53-HDM2 interaction. They tried to mimic key residues of p53 (Phe19, Trp23, Leu26), and identified compound 28 (Figure 6) as a selective inhibitor of this interaction, at a micromolar QSAR analysis of this type of oligoamide-based p53/HDM2 inhibitors was also carried out [71], studying hydrophobicity, electronic and steric effects, as well as H-bonding interactions, by changing para substituents on the benzyl ring of central Phe. These studies indicated that the dominant contribution on the inhibitory activity is the hydrophobic character of the central amino acid residue, due to the hydrophobic nature of the binding site.…”
Section: Oligomeric Amino Acid-containing Conjugatesmentioning
confidence: 99%
“…Sein Forschungsschwerpunkt ist der Einsatz von synthetischen Verbindungen, um molekulare Erkennung und Selbstorganisation zu verstehen und zu steuern, mit einer besonderen Betonung auf der Inhibierung von Protein‐Protein‐Wechselwirkungen. Er war gemeinsam mit Patrick T. Gunning Gastherausgeber von ChemBioChem ‐ und ChemMedChem ‐Sonderheften über Protein‐Protein‐Wechselwirkungen, und schrieb einen Beitrag über α‐Helix‐vermittelte Protein‐Protein‐Wechselwirkungen …”
Section: Ausgezeichnet …unclassified